STRATEGI PEMBERDAYAAN MASYARAKAT NELAYAN MELALUI PENGOLAHAN IKAN ASIN DI GAMPONG ALUE AMBANG KECAMATAN TEUNOM KABUPATEN ACEH JAYA - Handayani, Sri; Nasution, Aswin; Prayeta, Debby Olivia (Fakultas Pertanian, Universitas Janabadra, 2024)
The community empowerment strategy is a way to realize community capabilities and independence, especially from poverty and helplessness. The target group is 80 fishermen in Gampong Alue Ambang, Teunom District, Aceh Jaya Regency. This activity will be carried out from August to December 2022. The empowerment strategy carried out is through human resource development and productive business development. The research results show that knowledge and skills in developing human resources in Gampong Alue Ambang must continue to be carried out to form quality human resources based on knowledge and skills with all the potential that exists in them. Productive business development strategies can be implemented with 1). accessibility to fishing facilitie; 2). accessibility of the level of capital facilities; 3). accessibility to information sources; 4). business relations between fishermen and companies as well as market aspects. Another productive activity that can be carried out by fishermen is processing fish catches into salted fish.